2020
DOI: 10.1186/s13047-020-00387-y
|View full text |Cite
|
Sign up to set email alerts
|

Point‐of‐care bedside ultrasound examination for the exclusion of clinically significant ankle and fifth metatarsal bone fractures; a single blinded prospective diagnostic cohort study

Abstract: Objective The aim of this study was to assess the diagnostic value of point-of-care bedside ultrasound (PoCUS) as in usual clinical practice in suspected ankle and fifth metatarsal bone fractures, compared to the standard of radiographic imaging. Methods This prospective study included patients ≥17 years presenting to the Emergency Department with ankle trauma and positive Ottawa Ankle Rules. All patients underwent PoCUS of the ankle by a (resident) emergency physician, the images were assessed by an ultrasou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
(31 reference statements)
0
8
0
1
Order By: Relevance
“…In 10 studies, the reported sensitivity was >90%,8 23 25–32 but the sensitivity varied between 76% (95% CI 63% to 86%) and 100% (95% CI 29% to 100%) among studies (figure 2). In nine studies the reported specificity was at least 91%,8 22–24 26 28 29 31 32 but among all studies varied between 85% (95% CI 74% to 92%) and 100% (95% CI% 88% to 100%).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In 10 studies, the reported sensitivity was >90%,8 23 25–32 but the sensitivity varied between 76% (95% CI 63% to 86%) and 100% (95% CI 29% to 100%) among studies (figure 2). In nine studies the reported specificity was at least 91%,8 22–24 26 28 29 31 32 but among all studies varied between 85% (95% CI 74% to 92%) and 100% (95% CI% 88% to 100%).…”
Section: Resultsmentioning
confidence: 94%
“…A total of 1455 patients in 13 different studies were evaluated for bony injuries 8 21–32. All studies compared US with conventional X-ray (table 1).…”
Section: Resultsmentioning
confidence: 99%
“…This is in concordance with recent publications, which showed that ultrasound is an excellent initial assessment tool for long bone fractures with 90% sensitivity and specificity. 6,7 It should be mentioned that these studies also indicated that diagnostic accuracy for detecting long bone fractures depends on the operator experience.…”
Section: Discussionmentioning
confidence: 99%
“…A cohort trial compared the effects of mindfulnessbased cognitive therapy for children (MBCT-C) versus a psychoeducational waitlist control on symptoms of anxiety, emotion regulation, mindfulness, and overall clinical severity in 24 pediatric patients (9-18 years old) who had at least one biological parent with bipolar I disorder. 2 Patients were divided into four groups, with group 1…”
Section: Evidence-based Answermentioning
confidence: 99%